Tradition and Identity in the Revista de Historia Social y de las Mentalidades - Inostroza Ponce, Xochitl (Revista de Historia Social y de las Mentalidades, 2025)
Thirty years after its inception, the “Revista de Historia Social y de las Mentalidades” devotes this issue to the dossier “Invented Traditions and Cultural Stereotypes in Latin America, 19th and 20th Centuries,” which explores the construction of traditions through workers’ music, cultural exile, diplomacy, gastronomy, and the press, revealing the political, economic, and transdisciplinary dimensions of cultural history. The volume is rounded out by articles on photography, the press, and nationalist imaginaries in immigrant communities. All contributions engage in dialogue with one another and with RHSM’s critical and reflective vocation
Keywords: Invented traditions; Cultural History; transdisciplinarity